Effect of Season on Oocyte Recovery, Quality and Morphometry in Goat - SANGHA, G K; BHATIA, H; KHERA, K S (The Indian Journal of Animal Reproduction, 2023)
Seasonal effects have the potential to influence the follicular dynamics. The prerequisite for the contemporary embryo transfer technology is the availability of good quality oocytes. The present study was undertaken to observe effects of season on oocyte retrieval, quality and morphometry in goat. Maximum numbers of small (<3mm) as weH as large (>3mm) follicles were obtained during rainy season. The percentage recovery of oocytes was highest during rainy season though the proportion of good quality oocytes was more during winter. The size of the oocyte showed a direct relation with the follicular size. The diameter of small as well as large oocytes was reduced during summer. The present study reports a seasonal relationship of ovarian morphology as implicated by the quality of oocytes in slaughtered goats.